Risk indicators for severe impaired oral health among indigenous Australian young adults - Roberts-Thomson Kaye F; Jamieson Lisa M; Sayers Susan M (BMC, 2010)
Abstract Background Oral health impairment comprises three conceptual domains; pain, appearance and function. This study sought to: (1) estimate the prevalence of severe oral health impairment as assessed by a summary oral health impairment measure, including aspects of dental pain, dissatisfaction with dental appearance and difficulty eating, among a birth cohort of Indigenous Australian young adults (n = 442, age range 16-20 years); (2) compare prevalence according to demographic, socio-economic, behavioural, dental service utilisation and oral health outcome risk indicators; and (3) ascertain the independent contribution of those risk indicators to severe oral health impairment in this population. Methods Data were from the Aboriginal Birth Cohort (ABC) study, a prospective longitudinal investigation of Aboriginal individuals born 1987-1990 at an Australian regional hospital. Data for this analysis pertained to Wave-3 of the study only. Severe oral health impairment was defined as reported experience of toothache, poor dental appearance and food avoidance in the last 12 months. Logistic regression models were used to evaluate effects of demographic, socio-economic, behavioural, dental service utilisation and clinical oral disease indicators on severe oral health impairment. Effects were quantified as odds ratios (OR). Results The percent of participants with severe oral health impairment was 16.3 (95% CI 12.9-19.7). In the multivariate model, severe oral health impairment was associated with untreated dental decay (OR 4.0, 95% CI 1.6-9.6). In addition to that clinical indicator, greater odds of severe oral health impairment were associated with being female (OR 2.0, 95% CI 1.2-3.6), being aged 19-20 years (OR 2.1, 95% CI 1.2-3.6), soft drink consumption every day or a few days a week (OR 2.6, 95% 1.2-5.6) and non-ownership of a toothbrush (OR 1.9, 95% CI 1.1-3.4). Conclusions Severe oral health impairment was prevalent among this population. The findings suggest that public health strategies that address prevention and treatment of dental disease, self-regulation of soft drink consumption and ownership of oral self-care devices are needed if severe oral health impairment among Indigenous Australian young adults is to be reduced.